Drought Tolerance Strategies of Faba Bean Cultivars: Integrated Morphological, Physiological, and Biochemical Responses - Abdelsalam A. Shehab; Ahmed M. Abdelghany; Asmaa Hamoda; Elsayed Sh. Alwakel; Alsayed S. Farouk; Mohamed Ebaid; Sobhi F. Lamlom; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2026)
Water deficit stress significantly threatens faba bean productivity, highlighting the need to understand cultivar-specific drought tolerance mechanisms to improve breeding efforts. This study aimed to assess the morphological, physiological, and biochemical responses of three faba bean cultivars exposed to different drought levels during the vegetative and flowering stages. Three cultivars (Qidou2, Chenghu10, and Qinghai13) were subjected to different drought levels (35%, 55%, and 100% field capacity) during vegetative and blooming stages. Growth traits, root architecture, gas exchange, antioxidant enzyme activity, cuticular wax composition, and reproductive performance were systematically assessed. Different cultivars showed distinct tolerance patterns. Qidou2 had superior root growth, the highest water-use efficiency at 15.5 µmol CO₂ mmol⁻¹ H₂O, and a flower production tolerance index of about 2.0, indicating strong reproductive resilience. Chenghu10 demonstrated notable adaptability, including a 134% increase in relative intrinsic water-use efficiency under stress and elevated catalase activity at 405.75 U g⁻¹ min⁻¹. Qinghai13 showed moderate tolerance, maintaining steady photosynthesis at 10.33 µmol CO₂ m⁻² s⁻¹ and consistent enzyme activity. Cuticular wax deposition increased sharply during seedling stress (Qidou2: 6.464 to 9.845 µg cm⁻²). Reproductive traits were most stress-sensitive; for example, Qidou2 did not produce pods under severe drought despite vigorous growth. Overall, the findings highlight that coordinated responses across root architecture, physiology, metabolism, and protective barriers underpin drought adaptation. The diverse strategies identified across cultivars, from conservative water use to enhanced metabolic efficiency, provide valuable targets for breeding drought-resilient faba beans.